Impacts of development-induced displacement on urban locality and settlers: a case-study of the railway upgrading project in Metro Manila - Choi, N (2013)
Population displacement has long been a controversial companion of development. The central tension has been between the position challenging the kind of development that removes people from their homes, livelihoods and communities, and a managerial position that the impoverishment risks of displacement can be mitigated through an effective intervention. Whereas recent research has been devoted to unpacking a rather unsuccessful performance of involuntary resettlement as a mitigation measure, this study aims to question the assumption of mitigation itself by expanding the concept of development impacts beyond the realm of displacement. Through an empirical study of a railway project in Metro Manila, the Philippines, I examine how urban residents are affected by a large-scale demolition and displacement that took place in their locality. Semi-structured interviews were conducted along the railway tracks after the land was cleared of informal settlements since the study placed particular focus on residents who were not physically displaced. They are identified in my research as non-displaced people. Few studies have addressed the possibility that other people might have been adversely affected in situ and this is particularly so in urban areas. Empirical findings reveal that the physical environment and socio-economic relationships in the locality were significantly transformed through the clearance; impacting the tenure status, livelihoods and social milieu of non-displaced people. Tenure security was important for avoiding displacement but was not a definitive factor as a number of people are still informal settlers who continue to be faced with other eviction threats. For the non-displaced, the physical change of the locality became relevant when their productive capital, notably, a second house or business space, was affected. The loss or erosion of physical capital had a secondary impact on livelihoods, which was compounded by the rupture in the local livelihood network following a mass population outflow. Whereas the income of locally-based businesses decreased substantially, livelihoods that operate beyond the locality remain relatively resilient. Differentiated experiences of a local change are also reflected in a range of evaluations that describe local social ambiance before and after the event. Diverse ways in which non-displaced people were affected underline that the current conceptualisation of impacts is limited to one dimension of displacement. This raises the need to adopt a more holistic and disaggregated approach to understanding the complexities of development impacts. A discussion on whether and how they can be mitigated would benefit further from such a comprehensive study.